2021
DOI: 10.1038/s41467-021-22086-3
|View full text |Cite
|
Sign up to set email alerts
|

Universal resilience patterns in labor markets

Abstract: Cities are the innovation centers of the US economy, but technological disruptions can exclude workers and inhibit a middle class. Therefore, urban policy must promote the jobs and skills that increase worker pay, create employment, and foster economic resilience. In this paper, we model labor market resilience with an ecologically-inspired job network constructed from the similarity of occupations’ skill requirements. This framework reveals that the economic resilience of cities is universally and uniquely de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
29
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(39 citation statements)
references
References 34 publications
0
29
0
Order By: Relevance
“…As a result, our analyses and results are specific to the Australian labor market. However, this is a feature of our work rather than a limitation, as it allows to contextualize the analysis to geographical and temporal labor markets—it has been shown that labor markets can be highly contextual [ 39 ]. One can easily leverage our methods to produce results for other countries by applying equivalent country-specific labor market data from job ads, employment statistics, and occupational transitions.…”
Section: Resultsmentioning
confidence: 99%
“…As a result, our analyses and results are specific to the Australian labor market. However, this is a feature of our work rather than a limitation, as it allows to contextualize the analysis to geographical and temporal labor markets—it has been shown that labor markets can be highly contextual [ 39 ]. One can easily leverage our methods to produce results for other countries by applying equivalent country-specific labor market data from job ads, employment statistics, and occupational transitions.…”
Section: Resultsmentioning
confidence: 99%
“…As a proxy for a city's resilience, we calculated the ratio of inscriptions produced before and after 235 CE: a higher proportion of inscriptions produced after 235 CE is here interpreted as indicating higher economic resilience of a city in face of the third century crisis. Drawing on recent empirical studies of modern urban systems [10][11][12], we hypothesized that the cities with a higher sectoral diversity will reveal higher resilience than highly specialized cities.…”
Section: ) In the Case Ofmentioning
confidence: 99%
“…Diversity, on the other hand, is determined by the extent and equality with which employment is distributed across multiple industry sectors. While high sectoral specialization results in higher efficiency and greater economic productivity of a city as a whole, it also reduces urban resilience to change or shock [8,[10][11][12]. A modern example is Detroit whose focus on the car industry contributed to its economic eclipse in the end of the twentieth century [13].…”
Section: Introductionmentioning
confidence: 99%
“…Mechanistic approaches of this type have been successfully developed in recent years to address several societal challenges. Some relevant examples are: the identification of global systemic risks through financial networks [14], the universal description of urban growth and development across nations [15,16], the prediction of collective responses during emergencies [17], the dynamics of labor markets and their resilience to automation [18], and the understanding of gender inequalities in different contexts, from academic career trajectories [19,20] to human mobility aspects [21]. Other studies have investigated the dynamical evolution of ecosystems [22,23] and the impact of globalization on their resilience [24], as well as the quantification of the environmental impact of car sharing [25] or traffic mitigation [26].…”
Section: Introductionmentioning
confidence: 99%